PTH-098 Audit of Current Liver Biopsy Practice at A Single Tertiary Centre. (17th August 2016) - Harrison, R; Patanwala, I
Abstract : Introduction: In an era of increasing availability and access to well validated non-invasive laboratory diagnostic screens and measures of liver fibrosis, the role of liver biopsy for diagnosis and staging of liver disease has diminished. Liver biopsies are subject to sampling error which is made worse by inadequate sample sizes. There is no data on the adequacy of liver biopsy specimens when obtained percutaneously as opposed to the transjugular route.We aimed to assess the adequacy of liver biopsy samples as defined by the minimum standards suggested by the Royal College of Pathologists'(RCP), 1 UK (minimum of 6 portal tracts and sample length of 15 mm). Where available we wished to compare the results of biopsy fibrosis staging with transient elastography data. Methods: A retrospective study was designed to review all liver biopsy requests made in our tertiary liver unit between 31 st October 2012 and 24 June 2013. Results: 114 patients(59.6% male) with a median age of 48.7(interquartile range 19.8) had a liver biopsy. The commonest indications for biopsy were deranged liver function tests and queries regarding aetiology. Out of 114 reports 82 (71.9%) included the number of portal tracts and length of the biopsy and of these 52 (63.4%) were adequate samples as per RCP standards. 1 The number of transjugular liver biopsy reports were 16 (14.0%) and of these only 5 (31.3%) mentioned the size and number of portal tracts. Of these only 1 (20%) sample was adequate as per RCP standards. 1 Of the 98 (86.0%) percutaneous samples 77 (78.6%) reported the length and number of portal tracts and only 51 (66.2%) were adequate. Of the 114 patients, 54 (47.3%) had transient elastography within 12 months of the liver biopsy with 47 (87.0%) having a score above 7 kPa suggestive of abnormal liver stiffness. The 26 (48.1%) with a score above 12.2 kPa which is indicative of cirrhosis only 9 (34.6%) had a histological diagnosis of cirrhosis. Of the 13 (24.1%) patients who had a normal liver stiffness picture on transient elastography with a score below 7 kPa none had a histological diagnosis of cirrhosis. Conclusion: Assessment of sample adequacy was compromised because only two-thirds of the reports contained the recommended information to confirm adequacy. Of those where this information was present 36.6% of samples did not meet minimum standards set by the RCP 1 which may impact on histopathological diagnosis. The audit showed that patients with a low transient elastography were unlikely to have a histological diagnosis of cirrhosis. Patients with a raised transient elastography only a third were identified as being cirrhotic on biopsy suggesting further clinical correlation is required. Reference: 1 Wyatt J, et al . Tissue pathways for liver biopsies for the investigation of medical disease and for focal lesions Royal College of Pathologists' Guidelines. 2014. Disclosure of Interest: None Declared